2012
DOI: 10.1007/s11746-012-2151-6
|View full text |Cite
|
Sign up to set email alerts
|

Dragon Fruit (Hylocereus spp.) Seed Oils: Their Characterization and Stability Under Storage Conditions

Abstract: Oil was extracted from the seeds of white-flesh and red-flesh dragon fruits (Hylocereus spp.) using a cold extraction process with petroleum ether. The seeds contained significant amounts of oil (32-34 %). The main fatty acids were linoleic acid (C18:2, 45-55 %), oleic acid (C18:1, 19-24 %), palmitic acid (C16:0, 15-18 %) and stearic acid (C18:0, 7-8 %). The seed oils are interesting from a nutritional point of view as they contain a large amount of essential fatty acids, amounting to up to 56 %. In both drago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 17 publications
(37 reference statements)
0
52
1
3
Order By: Relevance
“…In addition, there is an increase in (tropical) fruit processing, generating large amounts of by‐products such as pomaces, peels and seeds. For instance, passion fruit consists of about 60% of inedible parts (FAO, ) and rambutan contains approximately 54% of peel and seed (Radha & Mathew, ), mango fruit have a high amount of peel (20–30%) and seed (10–15%) (Larrauri et al ., ; Abdalla et al ., ), and dragon fruit contains about 25% of peel and 8–8.6% of seed (Liaotrakoon et al ., ). Thus, valorisation of these by‐products is important and receives more attention as it is known that several nutritional and bioactive compounds are present in these fruit by‐products such as pigments, organic acids, antioxidants and fibresAguilar et al ., ; Aruldass et al ., ; Martínez et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, there is an increase in (tropical) fruit processing, generating large amounts of by‐products such as pomaces, peels and seeds. For instance, passion fruit consists of about 60% of inedible parts (FAO, ) and rambutan contains approximately 54% of peel and seed (Radha & Mathew, ), mango fruit have a high amount of peel (20–30%) and seed (10–15%) (Larrauri et al ., ; Abdalla et al ., ), and dragon fruit contains about 25% of peel and 8–8.6% of seed (Liaotrakoon et al ., ). Thus, valorisation of these by‐products is important and receives more attention as it is known that several nutritional and bioactive compounds are present in these fruit by‐products such as pigments, organic acids, antioxidants and fibresAguilar et al ., ; Aruldass et al ., ; Martínez et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…White 'pitaya' processing to extract the pulp generates a large quantity of residues, such as peels, which can be used for the extraction of betalains (betacyanins and betaxanthins) (Liaotrakoon et al, 2013;Mello et al, 2015). Liaotrakoon et al (2013) observed in 'pitaya ' (H. undatus and H. polyrhizus) peels that the polysaccharides of the cell wall contain expressive amounts of highly water-soluble methyl-esterified pectic substances, whereas Mello et al (2015) reported high concentrations of betalains in peels and mesocarp of pitaya (H. undatus), evidencing their potential as natural dye in food products, besides being rich in phenolic compounds and showing high antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Liaotrakoon et al (2013) observed in 'pitaya ' (H. undatus and H. polyrhizus) peels that the polysaccharides of the cell wall contain expressive amounts of highly water-soluble methyl-esterified pectic substances, whereas Mello et al (2015) reported high concentrations of betalains in peels and mesocarp of pitaya (H. undatus), evidencing their potential as natural dye in food products, besides being rich in phenolic compounds and showing high antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals, such as copper and iron, are effective promoters of radical reactions, reducing the activation energy of the oxidation reaction and increasing the rate of decomposition and formation of peroxides [5].Furthermore, during storage, the lipid fraction is gradually hydrolyzed by water or by natural lipolytic enzymes produced by bacterial and fungal contaminants. UV light can activate photosensitive compounds producing singlet states, forming additional peroxides [4,5].The oil composition (especially the fatty acid composition), the concentration of antioxidants, and the storage conditions (i.e., temperature, light, and oxygen) can have a significant effect on the quality of the oil during storage [6]. The changes are reflected by the acidity and oxidation indices.…”
mentioning
confidence: 99%
“…The oil composition (especially the fatty acid composition), the concentration of antioxidants, and the storage conditions (i.e., temperature, light, and oxygen) can have a significant effect on the quality of the oil during storage [6]. The changes are reflected by the acidity and oxidation indices.…”
mentioning
confidence: 99%